A biomimetic research on how cities can mimic forests to become sutainable and smart - KARABETÇA, ALİYE RAHŞAN (My University, 2020)
In nature, everything is functional concerning each other. Every single organism supports the other either with a symbiotic relationship or in terms of form and/or function; such as some trees shed their leaves to the ground to prepare themselves for strong winter conditions and also to create nutrition for microorganisms and fungi under the surface. This kind of interaction of nature could lead architects to develop better solutions to create better built environments which is the main objective of this paper. It aims to clarify and prove that nature is the greatest mentor and can teach humanity many solutions about designing smart cities. In this context, using biomimicry as a design strategy is the main methodology. Biomimicry and biology will be the scientific fields for researching and understanding the structural strength, bioclimatic properties, functional morphology and other important features of forests which will be explained to identify forests and state solutions for developing smart cities. Outcomes of this paper aim to scientifically state that forests are naturally sustainable built environments which are the greatest examples for smart cities and when they unite, they are able to create the most suitable living environments for other living organisms.
Keywords: Trees; Biomimicry; Smart Cities; Forests; Architecture; Ağaçlar; Biyomimikri; Akıllı Şehirler; Orman; Mimari